APPLICATION OF THE RAPID APPLICATION DEVELOPMENT METHOD FOR SALES INFORMATION SYSTEM FOR TRADITIONAL MINANG KABAU WEDDING DRESSES - Hendrato, Hening; Saefudin, Mohamad; Nada, Qothrun (Journal of Information System, Informatics and Computing, 2023)
The Minang Kabau shop system is running inefficiently because the data processing structure is still manual, causing a number of problems. Processing customer data, processing transactions and generating reports are the first steps that cause problems. To avoid data redundancy which costs the shop money, a Minang Kabau shop sales application was developed. Its purpose is to handle and process data stored in a database system. Rapid Application Development, often known as the RAD System Development Method, is used to develop this information system. To speed up the process, this development strategy involves reducing the development stages. Customer and transaction data processing capabilities are included in this Minang Kabau retail sales application. Thus, this application can facilitate data processing, report creation and processing of Minang Kabau store transactions.